Living with oropharyngeal dysphagia: effects of bolus modification on health-related quality of life—a systematic review - Swan, K.; Speyer, R.; Heijnen, B.; Wagg, B.; Cordier, Reinie (Springer, 2015)
Purpose - Difficulty swallowing, oropharyngeal dysphagia, is widespread among many patient populations (such as stroke and cancer groups) and aged community-dwelling individuals. It is commonly managed with bolus modification: altering food (usually cutting, mashing or puréeing) or fluids (typically thickening) to make them easier or safer to swallow. Although this treatment is ubiquitous, anecdotal evidence suggests patients dislike this management, and this may affect compliance and well-being. This review aimed to examine the impact of bolus modification on health-related quality of life. Methods - A systematic review of the literature was conducted by speech pathologists with experience in oropharyngeal dysphagia. The literature search was completed with electronic databases, PubMed and Embase, and all available exclusion dates up to September 2012 were used. The search was limited to English-language publications which were full text and appeared in peer-reviewed journals. Results - Eight studies met the inclusion criteria. Generally, bolus modification was typically associated with worse quality of life. Modifications to foods appeared to be more detrimental than modifications to fluids, but this may be due to the increased severity of dysfunction that is implied by the necessity for significant alterations to foods. The number of studies retrieved was quite small. The diverse nature of methodologies, terminologies and assessment procedures found in the studies makes the results difficult to generalise. Conclusion - Overall, even though the severity of dysphagia may have been a confounding factor, the impact of bolus modification on health-related quality of life in patients with oropharyngeal dysphagia appears to be negative, with increased modification of food and fluids often correlating to a decreased quality of life. Further, associated disease factors, such as decreased life expectancy, may also have affected health-related quality of life. More research is needed.